From St. Augustine and St. Denys to Olier and Bérulle’s Spiritual Revolution: Patristic and Seventeenth-Century Foundations of the Relations between Church and State in Québec - Hankey, Wayne J. (Laval théologique et philosophique, 2007)
By way of statutes on the façade of L’Hôtel du Parlement de Québec (especially Marie de l’Incarnation, Jean-Jacques Olier, and François de Laval), we explore the Augustinian and Pseudo-Dionysian foundations of the spirituality of New France. By way of records of the life there, and the textbooks used in them, we investigate the kinds of Augustinianism taught and inculcated at the Séminaire de Québec and the Grand Séminaire de Montréal ; particularly, we observe the passage from Gallican to Ultramontane ecclesiology. Olier’s surprising presence on the façade leads us to the Sulpicians and the political theology of the Cardinal de Bérulle. The Copernican revolution effected by this Dionysian hierarch brings a new interpretation of the sacrifice of Christ and the centrality of the priest. The institutional and ascetical implications of this new orientation in Christianity were worked out in New France far more completely than in the Hexagon. We conclude with a consideration of the character and role of the Catholic Church formed in this way in Post Conquest Québec and the consequences this had for the definitions of provincial and federal powers in the Canadian constitution. The Québec Church showed not only the enormous success modern clericalist and centralised Catholicism, with the seminary as its instrument, could achieve but also its limits.